2017
DOI: 10.1111/ajt.14427
|View full text |Cite
|
Sign up to set email alerts
|

Belatacept Rescue Therapy in Kidney Transplant Recipients With Vascular Lesions: A Case Control Study

Abstract: Immunosuppression in kidney transplant recipients with decreased graft function and severe histological vascular changes can be particularly challenging. Belatacept could be a valuable option, as a rescue therapy in this context. We report a retrospective case control study comparing a CNI to belatacept switch in 17 patients with vascular damage and low eGFR to a control group of 18 matched patients with CNI continuation. Belatacept switch was performed on average 51.5 months after kidney transplantation (6.2-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
16
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(21 citation statements)
references
References 21 publications
5
16
0
Order By: Relevance
“…We report that even in this relatively high‐risk group, renal function improved significantly by an average eGFR of 9.9ml/min/1.73m2. These results confirm and expand on previously published data [3‐9]. These studies had variable limitations related to lack of African‐American representation, absence of re‐grafts, sensitized patients, and the use of variable induction or maintenance immunosuppressive protocols.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…We report that even in this relatively high‐risk group, renal function improved significantly by an average eGFR of 9.9ml/min/1.73m2. These results confirm and expand on previously published data [3‐9]. These studies had variable limitations related to lack of African‐American representation, absence of re‐grafts, sensitized patients, and the use of variable induction or maintenance immunosuppressive protocols.…”
Section: Discussionsupporting
confidence: 89%
“…1). These findings mirror those noted in previous studies although a previous randomized controlled trial on this topic did show statistical improvement in eGFR beyond 12 months postconversion [4,7,25]. While ours was a review of a prospectively designed protocol, the primary limitation remains the lack of a randomized control group.…”
Section: Discussionsupporting
confidence: 88%
“…The group that was switched to belatacept experienced a statistically significant increase in mean eGFR at 6 months (30.4 mL/min) and 12 months (30.0 mL/min) compared to baseline. This was not true for the control group in which mean eGFRs at 6 and 12 months were both 24.7 mL/min …”
Section: Belataceptmentioning
confidence: 80%
“…Vascular constriction, including renal blood supply, could also contribute to the CNI‐induced renal dysfunction. A case series by Bertrand et al discusses the effects of switching the CNI in 17 kidney transplant recipients with vascular lesions and renal dysfunction to belatacept maintenance therapy after at least 6 months after transplant . The control group consisted of 18 similar patients who remained on CNI‐based therapy.…”
Section: Belataceptmentioning
confidence: 99%
“…Although the use of belatacept is associated with an increased risk of aTCMR, it has been shown to be a good alternative in KTRs with a contraindication to CNIs. Multiple studies have reported successful conversion to belatacept in KTRs with CNI-induced nephrotoxicity, impaired allograft function, delayed graft function, CNI-mediated thrombotic microangiopathy, or atypical hemolytic uremic syndrome [65][66][67][68][69][70][71][72][73][74][75][76][77][78][79][80][81][82]. Furthermore, KTRs with poorly controlled diabetes mellitus while receiving CNI therapy may benefit from belatacept [83,84].…”
Section: Clinical Outcomes After Conversion To Belatacept In Kidney Tmentioning
confidence: 99%